Курган зрубної культури в Північно-Східному Приазов’ї - Забавін, В.О.; Небрат, С.Г. (Археологический альманах, 2013)
Публікація присвячена матеріалам розкопок кургану в урочищі Гайдамацький Кут біля села Повлопіль на півдні Донецької області. Курган розташовувався на схилі вододілу лівого високого берега річки Кальміус (басейн Азовського моря). Авторами були досліджені 9 поховань зрубної культури. У статті розглядаються деякі питання поховальної практики носіїв зрубної культури. Статья посвящена публикации материалов раскопок кургана в урочище Гайдамацкий Кут возле села Повлополь на юге Донецкой области. Курган располагался на склоне водораздела левого высокого берега реки Кальмиус (бассейн Азовского моря). Авторами были исследованы 9 погребений срубной культуры. В статье рассматриваются некоторые вопросы погребальной практики. The paper is devoted to the publication of the excavated barrow in the natural boundary Gadamatsky kut near the village of Pavlopil in the South of Donetsk region. The barrow was located on the slope of watershed of the left high bank of the Kalmius river (Azov Sea basin). The authors have investigated 9 burials of the Timber-Grave Culture (Late Bronze Age). The article discusses some of the issues burial practices.